Possible role of hydroxylated metabolites of tacrine in drug toxicity and therapy of Alzheimer's disease - Patocka, Jiri; Jun, Daniel; Kuca, Kamil (Current drug metabolism, 2008)
Tacrine belongs to the group of acetylcholinesterse (AChE) inhibitors used as drugs for treatment of Alzheimer's disease (AD). The formation of hydroxyderivatives of tacrine is well-established step in the metabolization of this drug in liver by microsomal cytochrome P450 enzymes family. Genetic polymorphism of cytochrome P450 enzymes is probably responsible for balance between a number of stable and non-toxic metabolites and highly protein-reactive and toxic ones. By this manner may be explained why the hepatotoxicity of tacrine was observed only in the part of persons and why not every patient with AD responds to the treatment by this drug.
Keywords: cholinesterasové inhibitory; nootropní látky; Cytochrome P-450 Enzyme System; Tacrine; hydroxylace; Animals; takrin; Humans; Nootropic Agents; Cholinesterase Inhibitors; lidé; Alzheimer Disease; Hydroxylation; zvířata; Alzheimerova nemoc; systém (enzymů) cytochromů P-450